Mini Review of Breeding Program on Rubber Trees - Edi Wiraguna; Ade Astri Muliasari; Widya Hasian Situmeang; Agief Julio Pratama; Muhammad Iqbal Nurulhaq; Restu Puji Mumpuni; Hidayati Fatchur Rochmah; Merry Gloria Meliala; Aidil Azhar (Universitas Muhammadiyah Jember, 2023)
Rubber trees are one of the main tree crops in Southeast Asia that provides latex as the primary source of tire production. However, commercial clones of rubber trees are attacked by pests such as root and foliage diseases and are exposed to abiotic stresses such as drought, which make the development of resistant rubber clones to biotic and abiotic stresses crucial. This mini review highlights the breeding program to develop resistant rubber tree crops through crossing and biotechnology, including in vitro culture and genetic transformation.